Formulation Of Policy Perspective Of The Role Of Community Organizations Towards Pesantren Law - Fadlud Rozi (AIUA Journal of Islamic Education, 2020)
The formulation of public policy is the earliest step in the overall public policy process, because what happens at this stage will determine whether or not public policy is successful in the future. Therefore, there needs to be more prudence from policymakers when it comes to formulating this public policy. Also to keep in mind is that a good public policy formulation is a public policy formulation oriented towards implementation and evaluation. The role of policy-playing actors is crucial, including community organizations. One of the evidence now is the birth of the Pesantren Law.